Visual approaches to the representation of information in Belarusian children’s magazines of the 21st century - Kharytonоva, Sviеtlana V. (Journal of the Belarusian State University. Journalism, 2023)
The specificity of the translation of visual images by means of media design in children’s print media in the 21st century is determined. Trends in the modification of visual approaches to the representation of information in Belarusian journals intended for preschoolers, junior, middle and senior schoolchildren are revealed. Based on the design analysis of illustrative solutions for children’s magazines, the main directions of illustration are determined. In the group of periodicals for preschoolers and younger schoolchildren, the simplified stencil and professional art directions were identified. In the media text for middle and high school students, the ways of arranging non-verbal components are represented by a fragmentary and text-centric approach. It has been established that a culturally specific base for educating children in the field of the artistic content of Belarusian art and their aesthetic education is being created by several specialised publications, giving way to mass print media broadcasting fragmentary and simplified stencil solutions for visualising media text.
Keywords: children’s print media; approaches to information representation; illustration; visualisation of media text